2015
DOI: 10.1037/a0036993
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic differences in social anxiety between individuals of Asian heritage and European heritage: A meta-analytic review.

Abstract: Differences between Asian-heritage and European-heritage individuals have been found in both the prevalence and expression of social anxiety. Previous research suggests higher social anxiety among AH individuals, but both the methodology and the findings have been mixed and the effect sizes varied widely. The purpose of this meta-analytic study was to examine whether the AH/EH differences in social anxiety were robust across various moderators, and how these differences may be accounted by ethnic differences i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
38
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
2
2
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(50 citation statements)
references
References 114 publications
(213 reference statements)
9
38
1
Order By: Relevance
“…Additionally, the latent mean differences based on the partial scalar invariant measures were consistent with results of previous meta-analyses (e.g., Krieg & Xu, 2015) which showed higher social anxiety reported by individuals of Asian heritage than those of European heritage, providing some support for the validity of prior cultural comparisons. Furthermore, Study 2 showed that the majority of frequently mentioned descriptors by both cultural groups in response to the social anxiety vignette, such as 'symptoms of nervousness' and 'anxious', were negative attributes that are related to core features of social anxiety delineated in DSM, as well as the symptoms and experiences of social anxiety measured by SPS and SIAS.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…Additionally, the latent mean differences based on the partial scalar invariant measures were consistent with results of previous meta-analyses (e.g., Krieg & Xu, 2015) which showed higher social anxiety reported by individuals of Asian heritage than those of European heritage, providing some support for the validity of prior cultural comparisons. Furthermore, Study 2 showed that the majority of frequently mentioned descriptors by both cultural groups in response to the social anxiety vignette, such as 'symptoms of nervousness' and 'anxious', were negative attributes that are related to core features of social anxiety delineated in DSM, as well as the symptoms and experiences of social anxiety measured by SPS and SIAS.…”
Section: Discussionsupporting
confidence: 86%
“…The resulting latent mean difference was .28 (p = .01), indicating that Japanese scored higher than European Americans in social anxiety when equivalent measures were used. This is similar to the overall effect that Krieg and Xu (2015) found in their meta-analysis (d = .25).…”
Section: Latent Mean Difference In Social Anxietysupporting
confidence: 87%
See 2 more Smart Citations
“…In the 131 MASEM studies located, 123 of them used this approach. Seven studies (Fan, Jackson, Yang, Tang, & Zhang, 2010;Krieg & Xu, 2015;Montazemi, Pittaway, Saremi, & Wei, 2012;Murayama & Elliot, 2012;Simons, Leroy, Collewaert, & Masschelein, 2014;Trivette, Dunst, & Hamby, 2010;Yufik & Simms, 2010) used the two-stage SEM (TSSEM) approach, which will be introduced later. The remaining study (Grace et al, 2007) is the only study that used an approach similar to the parameter-based MASEM presented in the present paper.…”
Section: Applications Of Meta-analytic Structural Equation Modeling Imentioning
confidence: 99%